The Influence of Taxpayer Motivation and Awareness on Compliance in the Payment of Rural and Urban Land and Building Tax (PBB-P2) in Kuranji Sub-District - Faishol Arif; Boni Saputra (Darul Yasin Al Sys, 2026)
Compliance with the Rural and Urban Land and Building Tax (PBB-P2) is essential for strengthening regional fiscal independence; however, PBB-P2 revenue realization in Kuranji Sub-District, Padang City, declined from 72.87% in 2023 to 52.0% in 2024. This study aimed to analyze the partial and simultaneous effects of taxpayer motivation and awareness on PBB-P2 payment compliance. A quantitative causal-associative design was employed, involving 99 respondents selected through simple random sampling from a population of 7,257 taxpayers. Data were collected using a validated five-point Likert-scale questionnaire and analyzed through descriptive statistics and multiple linear regression. The findings showed that taxpayer motivation significantly affected PBB-P2 compliance (R² = 0.375, t = 7.626, p < .001), while taxpayer awareness also exerted a significant effect (R² = 0.495, t = 9.760, p < .001). Simultaneously, both variables explained 52.0% of the variance in taxpayer compliance (F = 54.010, p < .001), as represented by the regression equation Y = 5.481 + 0.306X₁ + 0.544X₂. Descriptive analysis classified taxpayer motivation as moderate (Respondent Achievement Level [TCR] = 64.0%), taxpayer awareness as moderate (TCR = 63.0%), and payment compliance as good (TCR = 67.6%). Taxpayer awareness emerged as the stronger predictor of compliance. The study concludes that improving PBB-P2 compliance requires coordinated interventions that strengthen both taxpayers’ motivation and awareness. These findings contribute empirical evidence on the behavioral determinants of local tax compliance and provide practical implications for designing targeted tax education, communication, and engagement strategies to increase PBB-P2 revenue and strengthen Padang City’s locally generated revenue.